The Effects of A Short Period of A Ketogenic Diet on Blood Biochemistry and Immunological Status in Overweight Thai Subjects - Lukseng, Thawatchai; Saetung, Chutipa; Khodom, Witthaya; Klangbud, Wiyada Kwanhian (Trends in Sciences, 2022)
Being overweight and obese is a fundamental health problem worldwide and is associated with many diseases. The ketogenic diet (KD) includes high fat and moderate protein, with the daily consumption of carbohydrates amounting to less than 10 % daily intake. KD is a popular choice for weight loss but has benefited many diseases, such as metabolic diseases and neurodegenerative disorders. Nonetheless, the effect of KD on overweight but healthy individuals is limited. Therefore, the objectives of the present study were to evaluate the effects of the KD program on the physical, blood biochemistry, hematological and immunological status of overweight, healthy individuals. The 9 overweight Thai women with body mass index (BMI) values over 25 kg/m2 participated in a self-conduct KD program for 28 days. The mean age of the group was 28.44 years. With 28-days of KD, a significant (p < 0.01) increase in blood ketone confirmed the ketosis status of participants. The mean blood ketone concentration increased from 0.41 ± 0.061 to 1.22 ± 0.267 mmol/L. Most of the participants’ physical parameters, such as body mass index (BMI), body weight, chest circumferences, hip circumferences, and arm circumferences, significantly decreased after 28-days of KD. Furthermore, the biochemistry indices (total cholesterol, triglyceride, LDL-C, and HDL-C) did not significantly differ from the baseline. However, fasting blood sugar decreased (p < 0.01) from 88.00 ± 1.014 to 83.78 ± 1.289 mg/dL. KD did not influence all hematological and immunological indices such as nitric oxide (NO) production (unstimulated and in 2.5 µg/mL PHA stimulation) and T cell subpopulations. Nonetheless, it increased NO production in 5 µg/mL PHA stimulation and mononuclear cell proliferation capacity (proliferation index). The data revealed that short-term KD in this study decreased participants’ physical body compositions and blood glucose levels. Moreover, the immune status after KD proved the immunomodulation effect of KD. HIGHLIGHTS Thai overweight subjects whose self-conducted 28-days ketogenic diet demonstrated Significantly decreased the bodyweight Significantly decreased the body compositions Significantly decreased blood sugar level. Significantly affected immune systems by increasing immune cell proliferation capacity and responding to the non-specific stimulator GRAPHICAL ABSTRACT